2014
DOI: 10.1021/cg500514c
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Twin Plane Re-entrant Edge Growth Mechanism at an Atomic Scale by Electron Microscopy

Abstract: We conducted an extensive electron microscopy study on surface and defect structures of boron suboxide/ suboxycarbide platelets by examining them under various imaging conditions, e.g., side-view and top-view perspectives. It was determined that a twin plane re-entrant edge mechanism was responsible for the growth process at an atomic scale. Moreover, this thorough investigation provided an opportunity to resolve several critical issues regarding this otherwise wellknown growth mechanism for metallic nanostruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…For example, prior studies showed that the formation of an impurity-based surficial “amorphous” films 1 (SAFs, as a type of surface complexions, where the term “complexion” refers to the thermodynamic equilibrium state of an interface; noting that this type of complexion is neither completely crystalline nor fully amorphous despite of being named as SAFs 1 ) - can change faceted particles into nanospheres 2 or stabilize anisotropic morphology 3 . Specifically, we have recently demonstrated that adding barium oxide as an additive along with the iron-rich catalyst can help to control the growth of B-C-O nanowires 4 and nanoplatelets 5 6 7 to achieve unique morphologies and high yields; here, we further demonstrated that the controlled anisotropic growth is related to the formation of barium-enriched surface complexions.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…For example, prior studies showed that the formation of an impurity-based surficial “amorphous” films 1 (SAFs, as a type of surface complexions, where the term “complexion” refers to the thermodynamic equilibrium state of an interface; noting that this type of complexion is neither completely crystalline nor fully amorphous despite of being named as SAFs 1 ) - can change faceted particles into nanospheres 2 or stabilize anisotropic morphology 3 . Specifically, we have recently demonstrated that adding barium oxide as an additive along with the iron-rich catalyst can help to control the growth of B-C-O nanowires 4 and nanoplatelets 5 6 7 to achieve unique morphologies and high yields; here, we further demonstrated that the controlled anisotropic growth is related to the formation of barium-enriched surface complexions.…”
mentioning
confidence: 61%
“…Stacking faults were frequently observed in boron-rich crystals and they were considered to arise from the instability in the iron boride catalysts, which assisted the continual nucleation of (001) ledges 7 . In some cases, we also observed trapped bilayers stabilized at stacking faults, similar to the situation of impurity segregation at grain boundaries 17 (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above results, it is clear that the growth pattern of Si primary dendrites has been changed as increasing the Si content in the Al-Si alloy. Generally, on solidi cation of the Al-Si hypereutectic alloy, the growth of plate-like Si primary dendrites lies on (111) planes and in [211] directions, where it occurs by the twin plane re-entrance edge (TPRE) mechanism [24]. Figure 8(a) illustrates schematically the growth model of the plate-like Si primary dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the plate-like Si primary dendrites have a sharp tip morphology along < 211 > fast growth direction [24], which would be easily broken due to its fragile property, especially surrounded by plenty of neighboring grains. The broken tip usually has small size (< 0.5 mm, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental Section. Boron-containing low-dimensional materials were prepared with high reproducibility by a high-temperature solid state processing (that was referred to as “sintering” in prior studies, ,, despite the fact that it is not the same as the sintering processing as conventionally defined in ceramics), with a starting precursor of BaO, B, and Fe 3 O 4 in a molar ratio of 1.04:16.11:1. First, the starting powder was ground to fine particles with the addition of 0.1 mL glycerol to assist the high yield growth .…”
mentioning
confidence: 99%